Phenolics Profiling and Free Radical Scavenging Activity of Annona muricata, Gynura procumbens, and Typhonium flagelliforme Leaves Extract - Dewi Anggraini Septaningsih; Amalia Yunita; Cecep Abdurohman Putra; Irma Herawati Suparto; Suminar Setiati Achmadi; Rudi Heryanto; Mohamad Rafi (Universitas Gadjah Mada, 2021)
The leaves of Annona muricata (sirsak), Gynura procumbens (sambung nyawa), and Typhonium flagelliforme (keladi tikus) have been used as traditional medicines in Indonesia. This study aims to determine the antioxidant capacity and putatively identified phenolics from the leaves of three medicinal plants forementioned above. We used the DPPH (2,2-diphenyl-1-picrylhydrazyl) method for measuring radical scavenging (antioxidant assay) while the phenolics profiling was determined using UHPLC-Q-Orbitrap HRMS. The results showed that the percentage of radical scavenging activity of G. procumbens leaves extract in ethanol was higher than the other two plants. Phenolics profiling of the three medicinal plants was identified with 38 compounds belonging to flavones and flavanols hydroxycinnamic acid, and several other groups. The number of metabolites identified putatively was 12, 31, and 19 metabolites in the extracts of A. muricata, G. procumbens, and T. flagelliforme, respectively. The results confirmed the correlation between the phenolics presence and the antioxidant capacity of three plants used in this study.